Bi-axially oriented polystyrene/montmorillonite nanocomposite films. Issue 72 (6th August 2015) - Huang, Wenhan; Zeng, Songshan; Liu, Jingjing; Sun, Luyi
<x xml:space="preserve">Abstract</x> Polystyrene (PS)/montmorillonite (MMT) nanocomposite films were prepared by bi-axially stretching compounded and extruded PS/MMT nanocomposite sheets, resulting in an improved level of exfoliation and orientation during stretching.